Modern fitness technologies and their impact on population health - Abrashina I.V. ,; Popova E.V. ,; Soldatova M.A. ,; Titovets S.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine contraindications to the most popular areas of fitness and to identify the validity of the stated results of such techniques as bodyflex and crossfit. Methods and structure of the study. Theoretical substantiation of practical research experience, analysis of scientific and methodological literature (comparisons, analogies, induction). Results and conclusions. An analysis of modern trends in fitness is presented, contraindications to certain types of physical activity are indicated. Contradictions between individual hypotheses and the scientific substantiation of the impact on those involved in such sports as bodyflex and crossfit were revealed. Due to insufficient knowledge of the influence of modern trends in fitness on the body of those involved, a recommendation is made for a professional attitude towards little-studied techniques.